Pancreatoblastoma masquerading as hepatoblastoma: A diagnostic dilemma - Aruna Prabhu; Monica Bhagat; Mukta Ramadwar; Sajid S Qureshi (Wolters Kluwer Medknow Publications, 2016)
Clinicoradiological and histopathological differentiation of pancreatoblastoma from hepatoblastoma can often be a challenge in clinical practice owing to their peculiar resemblance. We report a case of a 4-year-old boy with a right hypochondriac region mass, which was diagnosed as hepatoblastoma on the basis of imaging, raised tumor marker, and biopsy; however, pancreatic origin of the mass was ascertained on exploration and pancreatoblastoma was confirmed on histopathology.